Tanggung jawab jasa pengiriman barang atas hilang dan rusaknya barang berdasarkan UU Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen: (Studi Kasus PT. Hj. Warni Niode Palu) - Randi Randi; Weny Almoravid Dungga; Dolot Alhasni Bakung (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine civil liability related to default in article 7 letter f of law No. 8 of 1999 concerning consumer protection at PT. Hj. Warni Niode Palu, as well as to know and understand the process of resolving disputes related to this default through ADR (Alternative Dispute Resolution), namely dispute resolution outside the court. This type of research is a normative-empirical research, namely research conducted by conducting field research, and using a quantitative approach to primary data and secondary data. Primary data includes interviews with the parties concerned, namely PT. Hj. Warni Niode Palu as a provider of transportation services and service users (consumers) and secondary data includes a search of the literature as a support for the main data. Based on the results of the study, the researchers concluded that the responsibility of the Freight Forwarding Services of PT. Hj. Warni Niode is based on Article 7 letter F of Law no. 8 of 1999 concerning Consumer Protection, namely the provision of compensation for compensation for traded services, has proven to be not optimal, PT. Hj. Warni Niode does not provide compensation in accordance with the amount of losses suffered by PT. Sari Jasa. Therefore, PT. Hj. Warni Niode was declared in default because it was not in accordance with what had been agreed upon and mutually agreed upon. The solution sought is a settlement through Alternative Dispute Resolution (ADR), especially mediation, as an efficient and fair way of resolving disputes between PT. Hj. Warni Niode and PT. Sari Jasa to avoid time-consuming litigation.